MOST FREQUENT WORDS USED IN PRIDE AND PREJUDICE’S NOVEL AND MOVIE - Septi Haryati; Homsatun Nafiah (Department of Master of Linguistic, Universitas Airlangga, 2023)
Abstract Altering a novel into a screenplay has been recorded as the interesting process in the field of literary works. There will be a number of adjustments that become consideration of the director particularly dialogues. This research aims to analyze the lexical differences used by Pride and Prejudice story in both novel and movie’s version. Also, the researchers strive to interpret the results based on the highlight of each text. The novel and movie script are converted into .txt format, and using AntConc device to sort the 50 highest words used by those sources. Then, the word list is categorized based on the part of speech by Mulyana (2013). The findings reveal that in the fifty word list, most of the lexical results include in the part of speech categories except Adjective and Exclamation. Thus, the first rank in the word list is positioned by the article (the) with the number of 918 times used in the movie and 4330 times used in the novel. The dominant issue can be portrayed through observing the noun and pronoun. They chiefly indicate the gender issue experienced by the main character of the story.